2022
DOI: 10.34659/eis.2022.81.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Supporting local economic development as a motive for purchasing organic food

Abstract: The aim of this paper is to assess the significance of organic food purchases by consumers in Poland – motivated by supporting the local economy – against the background of other factors shaping consumer behaviour. The empirical material consists of the results of a survey among 850 consumers of organic food in Poland.  The empirical material was analysed using Pearson’s chi-squared test of independence and the non-parametric Mann–Whitney U test. The study shows that for a large group of organic food consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…A study of Czudec et al (2022) has revealed stronger environmental motivations. For a significant percentage of organic consumers, the motivation is to support the local economy (51%), of which up to 65% indicated concern for the environment as one of the five most important motives for purchasing organic food [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Czudec et al (2022) has revealed stronger environmental motivations. For a significant percentage of organic consumers, the motivation is to support the local economy (51%), of which up to 65% indicated concern for the environment as one of the five most important motives for purchasing organic food [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…(20,8 mld euro w 2012 r. vs. 37,4 mld euro w 2018 r.) (EP 2021). Należy dodać, że również w Stanach Zjednoczonych oraz w krajach europejskich w omawianym okresie wzrastał popyt na produkty z upraw ekologicznych, czego odzwierciedleniem było prawie 10% udziału ekożywności w całkowitym rynku żywności w USA i Niemczech oraz 20% w Danii (Czudec, Miś, Zając 2022;Gryn 2020;Ham 2019;Mulder, Liu 2017;Ruiz de Maya, López-López, Munuera 2011). Szacuje się, że w 2019 r. na świecie było co najmniej 3,1 mln ekoproducentów, w tym 51% pochodziło z Azji, 27% z Afryki, 14% z Europy, a 7% z Ameryki Łacińskiej.…”
Section: Wprowadzenieunclassified
“…(from 10 047 896 ha in 2012 to 13 438 168 ha in 2018), and a significant increase in sales of organic food was recorded in this period (from 20.8 billion in 2012 to 37.4 billion in 2018) (European Parliament, 2018). Also, in the USA and in Europe, it grew steadily, which manifests itself in a nearly 10% share of organic food in the food market in the USA and Germany and a 20% share in Denmark (Mulder & Liu, 2017;Gryn, 2020;Czudec et al, 2022). Organic food is also becoming increasingly popular in France, the UK and Switzerland (Ruiz de Maya et al, 2011;Ham, 2019) (Figure 1).…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…This may provide many diverse benefits, and consumers will enjoy healthy products of high quality and sensory value. An increase in organic food production will help to increase the farmers' income and use the existing labour resources on farms more effectively and protect the natural environment (Czudec et al, 2022). The popularity of organic food is also increasing in Poland because increasingly aware consumers are seeking healthy, GMO-free food (Witek & Szalonka, 2017), without pesticides and allergising or harmful additives, preferably in biodegradable packaging (Witkowska-Dąbrowska et al, 2020).…”
Section: An Overview Of the Literaturementioning
confidence: 99%